The The Influence of Learning Facilities, Learning Motivation, Study Discipline, and Parental and Peer Support on Student Academic Achievement - Salsa Billa; Nora Susanti; Gustia Harini (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to analyze the influence of learning facilities, learning motivation, learning discipline, parental support, and peers on the academic achievement of Grade X AKL students in the Basic Accounting subject at SMK N 2 Padang, both directly and indirectly through learning motivation and learning discipline as intervening variables. The study employs a quantitative approach using descriptive and associative methods. The research population consists of all Grade X AKL students, with a sample size of 106 respondents. Data analysis includes path analysis and hypothesis testing (t-test) using SPSS version 25. The results indicate that learning facilities have a positive and significant effect on learning motivation but no effect on learning discipline; parental support has no effect on learning motivation but has a positive and significant effect on learning discipline; peers have a positive and significant effect on learning motivation but no effect on learning discipline; learning motivation has a positive and significant effect on learning discipline; learning discipline has a positive and significant effect on learning motivation; learning facilities have no effect on academic achievement; parental support has no effect on student academic achievement; peers have a positive and significant effect on student academic achievement; learning motivation has a positive and significant effect on student academic achievement; and learning discipline has no effect on student academic achievement.